2018
DOI: 10.3390/batteries4040061
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Rechargeable Batteries with Electrolytes Based on Nafion Membranes Intercalated by Mixtures of Organic Solvents

Abstract: The possibilities of manufacturing batteries with Nafion 117 membranes in the Na+-form intercalated by mixtures of non-aqueous organic solvents used both as an electrolyte, separator, and binder were investigated. Electrochemical stability of various organic solvent mixtures based on N,N-dimethylacetamide, ethylene carbonate, propylene carbonate, and tetrahydrofuran were characterized. It was shown that a sodium battery based on a Nafion-Na membrane intercalated by mixture of ethylene carbonate and propylene c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In [1], the electrochemical stability of sodium perchlorate in mixed organic solvents was estimated in studying the possibility of creating low-temperature batteries with sodium metal as the negative electrode and modified Nafion membrane as the electrolyte. Solutions were studied in binary mixtures of ethylene carbonate (EC)-dimethylacetamide (DMAA), ECpropylene carbonate (PC), and EC-tetrahydrofuran (THF), ternary mixtures of EC-diethyl carbonate (DEC) and PC-DMAA-THF, and a four-component mixture of EC-PC-THF-DMAA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [1], the electrochemical stability of sodium perchlorate in mixed organic solvents was estimated in studying the possibility of creating low-temperature batteries with sodium metal as the negative electrode and modified Nafion membrane as the electrolyte. Solutions were studied in binary mixtures of ethylene carbonate (EC)-dimethylacetamide (DMAA), ECpropylene carbonate (PC), and EC-tetrahydrofuran (THF), ternary mixtures of EC-diethyl carbonate (DEC) and PC-DMAA-THF, and a four-component mixture of EC-PC-THF-DMAA.…”
Section: Introductionmentioning
confidence: 99%
“…Some reports in the literature have also shown that DMAA additives in the standard Li ion battery electrolyte (a solution of LiPF 6 in EC-DEC-dimethyl carbonate mixture) have some stabilizing effect at increased temperatures [3]. How-ever, it was found in [1] that all DMAA-containing solutions have reduced electrochemical stability, and they are oxidized at relatively low anode potentials.…”
Section: Introductionmentioning
confidence: 99%
“…The Nafion membrane conductivity is significantly improved with the absorption of water or other solvents due to the formation of a system of pores and channels within the membrane that contains the solvent molecules and the cations produced by the dissociation of functional groups . Applied to use in LIBs, the membranes are usually intercalated by organic solvents that are deployed in liquid electrolytes, such as propylene carbonate as well as mixtures of propylene and ethylene carbonate, ethylene and diethyl carbonate, etc. However, such Nafion-based solvates are often characterized by rather low ionic conductivity (<10 –4 S/cm at room temperature). The use of certain sulfoxides or amides, for example, dimethyl sulfoxide, N , N -dimethylformamide, or N -methylformamide, makes it possible to achieve higher values of ionic conductivity (10 –3 S/cm at room temperature) due to better solvation. The pretreatment of Nafion membranes with low molecular weight polar solvents, such as aliphatic alcohols, followed by drying can lead to an increase in the ionic conductivity of the Nafion by an order of magnitude when impregnated with organic carbonates .…”
Section: Introductionmentioning
confidence: 99%